Architectural practice & construction management : the new ladder type curriculum - Salvan, George Salinda (Makati City, Philippines : Goodwill Trading Co, Inc., 2005)
This book is intended as a reference for all the managers of design practice, whether they can be professional architects or engineers who have assumed management roles in their firms, or trained managers who have chosen to apply their skills in design firms. The book is divided into three parts. First part dealing on all the laws pertaining to labor, civil, building laws, fire codes, law on the practice of architecture, the purpose of which is to inculcate upon the student, the legal obligations, duties and responsibilities of the Architect. To give the student sufficient mastery in using the building code, and other laws related to land development and human settlements. To give the student an understanding of building contracts and duties of a building inspector. The second part deals with the Administering the regular services of the Architect. Here the student is provided with the basic requirements of how the architect can fulfill the roles of a responsible professional. He is provided with tools in efficient conduct of client relations. The students is also provided with the background knowledge in properly administering the production of documents for building designs and construction projects Part Three is geared towards the comprehensive Services of the architect. The subject matter are arranged to provide student with further knowledge of the architect;s broader role in practice. He is given basic skills and techniques in project management. Another purpose is to equip the student with basic tools in resource allocation competence in inter-professional coordination necessary for the fulfillment of comprehensive services of the architect. As for students of civil engineering, the third part is recommended as it deals with constructive management, preparing Feasibility studies, the planning and scheduling of contruction work or pert-cpm, the specification writing and most importan of allm the procedure in letting our or joining a Bid in Construction.
Keywords: CONSTRUCTION INDUSTRY